The preparation of the environmental reconstruction of the Csörsz-ditch with GIS - Harkányiné Székely, Zsuzsanna; Benő, Dávid; Prunner, Andrea; Katona, Andrea (JOURNAL OF LANDSCAPE ECOLOGY, 2008)
The Csörsz Ditch (also known as Ördög - or in English The Devil’s Ditch") is an earthwork spanning a total of 1260 kms that enfolds the Great Hungarian Plain. The width of the ditch varies from 3.4 to 8 m. Its depth is 1.5–3 m from the current surface. The surviving parts of the vallum are about 2 m high. The system is composed of two, three, or even, at several points, four lines. The starting point of the ditch is the bank of the Danube, almost opposite Aquincum, the capital of Pannonia Inferior. From here it runs almost exactly from east to west and turns to the south below Nyíregyháza. From here it passes the eastern part of the Hungarian Plain, crosses the Banat and ends at the lower Danube opposite Viminacium in Moesia Superior. The Csörsz-ditch maybe constructed by nations Sarmatae, environ the II-III. century. The archeologists don’t know exactly why does it building for. At the bord-line of Gödöllő and Valkó we can identify the ditch. Our work concentrates for that area, because here the ditch we found in a very good estate. In the course of our work we used the three Hungarian military survey’s maps and topographic maps. For first we roamed the department of Csörsz-ditch’s near Gödöllő and we use a GPS to identify the ditch in digital form. On the first military survey’s map (between 1763–1787) we can find the Csörsz-ditch , but forasmuch it hasn’t got a projection base, we cant put into a GIS, but it has gave us some very important information about the ditch. The second (between 1819–1869) and the third military survey’s maps (1869–1887) have a projection base and hereby we can use that in ArcView 3.0. You can see that two maps where we sign the ditch what we found in the other maps and our GPS points too. On the topographic map, we can identified the line of the ditch, but signed like a road, not like a ditch, that is why we want to concrete that line and draw to the present-day maps signed as a ditch. In the future we will want to realize a complete environmental reconstruction in a court department of Csörsz-ditch near Gödöllő, to establish a study path along the ditch. After all we want to take it into the tourism, because in Gödöllő there is only one of sight: the Castle of Grassalkovich.